2012
DOI: 10.1155/2012/138680
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Chest Pain, Depression, Somatization, Anxiety, Global Distress, and Substance Use among Cardiac and Pulmonary Rehabilitation Patients

Abstract: Psychosocial factors of cardiovascular disease receive a preponderance of attention. Little attention is paid to psychosocial factors of pulmonary disease. This paper sought to describe psychosocial characteristics and to identify differences between cardiac and pulmonary patients entering a phase II rehabilitation program. Parametric and nonparametric analyses were conducted to examine scores on the Brief Symptom Inventory-18 (BSI-18) and the CAGE-D, administered at entry as standard clinical care. Participan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 24 publications
0
3
0
Order By: Relevance
“…It is directly related to the sense of well-being, quality of life, and health care expenses [ 10 , 11 ]. The study of somatic symptom burden has attracted the interests of researchers from different parts of the world and researchers have studied it in common clinical conditions such as anxiety, depression, chronic obstructive pulmonary disease (COPD), and cardiac illnesses [ 12 - 14 ]. In a large study involving 1,329 patients with anxiety and depression disorders, it has been found that 72.2%, 20.7%, and 7.1% of patients had a minimal/mild, medium, and high level of somatic symptom severity, respectively [ 12 ].…”
Section: Discussionmentioning
confidence: 99%
“…It is directly related to the sense of well-being, quality of life, and health care expenses [ 10 , 11 ]. The study of somatic symptom burden has attracted the interests of researchers from different parts of the world and researchers have studied it in common clinical conditions such as anxiety, depression, chronic obstructive pulmonary disease (COPD), and cardiac illnesses [ 12 - 14 ]. In a large study involving 1,329 patients with anxiety and depression disorders, it has been found that 72.2%, 20.7%, and 7.1% of patients had a minimal/mild, medium, and high level of somatic symptom severity, respectively [ 12 ].…”
Section: Discussionmentioning
confidence: 99%
“…Up to 20% of patients with coronary heart disease meet diagnostic criteria for major depression, and up to 47% report significant and long-lasting depressive symptoms (Bush et al, 2005 ; Carney and Freedland, 2008 ). Recent reports have indicated that this effect is not restricted to individuals with cardiovascular disease, as patients undergoing rehabilitation for pulmonary disease were even more likely than cardiac patients to exhibit clinically significant depression and psychological distress (Serber et al, 2012 ). Cardiovascular risk factors are pathologically relevant even prior to diagnosis.…”
Section: Systemic Disorders Associated With Depressionmentioning
confidence: 99%
“…The Brief Symptom Inventory-18 (BSI-18; Derogatis, 2001) is an 18-item Self-Report Checklist measure developed as a brief screen for psychological symptoms in medical patients. The BSI-18 has been widely used in research and clinical applications with a variety of patient populations (e.g., Derogatis & Melisaratos, 1983; Mustanski, Garofalo, Herrick, & Donenberg, 2007; Petkus et al, 2010; Serber et al, 2012), including oncology samples (Bober et al, 2013; Galdon et al, 2008; Kwak et al, 2013b; Merport, Bober, Grose, & Recklitis, 2012; Michel, Rebholz, von der Weid, Bergstraesser, & Kuehni, 2010; Michel & Vetsch, 2015; Zabora, 2015; Zabora et al, 2001; Zeltzer et al, 2009). Application of the BSI-18 to oncology patients is supported by its brevity, its coverage of the critical areas of anxiety and depression, and the published manual’s inclusion of normative data for an oncology sample.…”
mentioning
confidence: 99%